Predicting the mental health of rural Bangladeshi children in coronavirus disease 2019 - Moon, Nazmun Nessa; Hossain, Refath Ara; Jahan, Israt; Shakil, Shahriar; Uddin, Shihab; Hassan, Mahmudul; Nur, Fernaz Narin (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The novel coronavirus disease 2019 (COVID-19) current pandemic is a worldwide health emergency like no other. It is not the only COVID-19 infection in infants, children, and adolescents that is causing concern among their families and professionals; there are also other serious issues that must be carefully detected and addressed. Major things are identified due to COVID-19, some elements are affecting children’s healthcare in direct or indirect ways, affecting them not just from a medical standpoint but also from social, psychological, economic, and educational perspectives. All these factors may have affected children’s mental development, particularly in rural settings. As Bangladesh faces a major challenge such as a lack of public mental health facilities, especially in rural areas. So, we discovered a method to predict the mental development condition of rural children that they are facing at this time of COVID-19 using machine learning technology. This research work can predict whether a rural child is mentally developed or mentally hampered in Bangladesh and this prediction gives nice feedback.